PENYITAAN BARANG BUKTI DALAM PELANGGARAN LALU LINTAS - Elias Zadrach Leasa (Faculty of Law, Universitas Pattimura, 2015)
In Law Number 22 Year 2009 regarding Traffic and Road Transportation, regulates road vehicle inspections and enforcement in the form of a ticket is accompanied by forfeiture of evidence. The foreclosure can be a vehicle and motor vehicle papers as evidence relating to the violation. Police investigators and civil servants in the field of Traffic has the authority to conduct the investigation. Police investigators have authority over the confiscation of objects/evidence in a traffic violation, according to the prosecution examination of motor vehicles on the road. The seizure may be made to the letters of a motor vehicle such as driver's license, vehicle registration and motor vehicles. However, in the elaboration of the Government Regulation No. 80 Year 2012 on the Motor Vehicle Inspection Procedures governing the relationship between the physical evidence seized by the violations. The traffic police are expected to behave professionally in confiscating objects or items of evidence in accordance with violations.